Industry clusters and innovation in the Arab world : challenges and opportunities - Ebrashi, Raghda El; Hattab, Hala; Hassan, Rasha; Bouchra, Nancy (Emerald Publishing Limited, 2023)
Industry clusters promote innovation in the Arab World, through collaboration among businesses, research institutions, and governments. Benefits include the creation and sharing of knowledge, professional networking, access to spill-over knowledge, and specialized talent pools. These are the necessary elements to support the blossoming of innovation. In addition, clusters have the capacity to foster economic development in the region as a whole. They are key determinants in improving micro and small firms' performance through company linkages and access to internationalization opportunities. Industry Clusters and Innovation in the Arab World presents research and case studies in a range of Arabic-speaking countries, and proposes a series of reforms to build and promote industry clusters in the region. Challenges facing the establishment and the competitiveness of such clusters are also explored, and real-world applicable recommendations are provided. This break-through research highlights opportunities, and also macro-environmental threats. This is essential reading for researchers, policy-makers, and practitioners.
Keywords: Industrial clusters -- Arab countries.; Technological innovations -- Arab countries.; Business & Economics -- Industries -- General.; Industry & industrial studies.; elektronické knihy; electronic books